Cyclists do not need to incorporate off-bike resistance training to increase strength, muscle-tendon structure, and pedaling performance: Exploring a high-intensity on-bike method - Pallares, Jesús G.; Barranco-Gil, David; Rodríguez-Rielves, Víctor; de Pablos, Raúl; Buendía-Romero, Ángel; Martínez-Cava, Alejandro; Franco-López, Francisco; Sánchez-Redondo, Iván R.; Iriberri, Jon; Revuelta, Carlos; Lillo-Bevia, José Ramón; Valenzuela, Pedro; et al. (Biology of Sport, 2025)
This randomized controlled trial compared the effectiveness of high-intensity off- and on-bike resistance training (RT) in well-trained cyclists. Thirty-seven cyclists incorporated into their cycling routine a 10-week RT only differing in the exercise used: full squat (off-bike RT, n = 12) or high-intensity all-out pedaling efforts (on-bike RT, n = 12). RT variables like intensity (% maximal dynamic force, MDF), volume, sets, and rest were identical between groups. A third group of cyclists who continued their cycling routine but did not include additional RT stimuli was used as a control ( n = 13). The cycling volume at each intensity zone was also matched between the three groups. No significant differences were found between off- and on-bike RT in any parameter. RT groups improved the maximal aerobic power (ES ≥ 0.37) and that attained at the respiratory compensation point (RCP, ES ≥ 0.20). The on-bike RT also significantly enhanced power attained at the ventilatory threshold (ES = 0.24). Off-bike MDF was meaningfully enhanced by both RT groups (ES ≥ 0.16), whereas the on-bike group also significantly increased pedaling MDF (ES = 0.67). Quadriceps size was significantly increased by the off-bike group (ES = 0.22), whereas the on-bike RT also tended to augment this parameter (ES = 0.15) and patellar tendon size (ES = 0.35). Improvements in both RT regimes for time-to-exhaustion capacity (ES ≥ 0.30) were considerable but not significant. The off-bike group tended to increase injury-related symptoms (ES ≥ 0.33). The control group significantly decreased off-and on-bike MDF (ES ≤ -0.40) and quadriceps size (ES = -0.26). These findings suggest that high-intensity on-bike RT is an effective alternative to off-bike RT to safely increase strength, muscle-tendon structure, and cycling performance.